Knowledge, Attitude and Practice towards COVID-19 among Undergraduate Students in Nepal - Budha Magar, Esther; Khushbu Deo (Asian Journal of Medical Sciences, 2022)
Background: Nepal is a landlocked country standing highly vulnerable to unfolding pandemic. As per a UNDP survey in May, three in five employees had lost their job during COVID-19 and most of them were youths. During the first 74 days of lockdown, 16 people committed suicide per day (total 1227 cases). Hence, the main objective of the study was to assess knowledge, attitude, and practice toward COVID-19 in undergraduate students of Nepal.Aims and Objectives: This study aims to assess the knowledge, attitude, and practice among undergraduates of Nepal.Materials and Methods: This study is a cross-sectional study conducted among undergraduates residing in Nepal through online Google Forms for the conduction of online survey using purposive sampling technique. The participants were called through social media and the process about the use of Google Forms was explained by the researcher. The questionnaires were taken from open-access pre-published article. Univariate and bivariate analyses were applied for assessing knowledge, attitude, and practice and their association with independent variables.Results: In this study, among the 120 respondent who had agreed to take part in the research study, the overall knowledge level was found to be high toward COVID-19 among Nepalese undergraduates (Mean=0.74, SD=0.16), Majority of the participants, that is, 92.5% of participants had positive attitude regarding improved immunity as a measure to protect from COVID-19 and had good practice to prevent COVID-19 (Mean=0.84, SD=0.28).Conclusion: The knowledge was found to be high. Furthermore, optimistic attitude and proactive practice was seen among the undergraduates toward the battle against this pandemic. Contradiction to previous studies, significant association of provincial habitat with attitude towards COVID-19 was found.